A Comparative Analysis of the Expectations Hypothesis of the Term Structure of Interest Rates between the BRICS and G7 Countries - Muzindutsi, Paul‑Francois; Mposelwa, Sinethemba (Comparative Economic Research. Central and Eastern Europe, 2021)
This paper examines the predictive ability of the expectations hypothesis of the term structure of interest rates in the BRICS and G7 countries by relating each country’s monthly 3‑month Treasury bill rate to 10‑year government bond rates, from May 2003 to May 2018. The panel ARDL model, applying the mean group (MG), pooled mean group (PMG), and dynamic fixed effects (DFE) estimators, is employed to compare the short‑ and long‑run relationships in both groups of countries. The results show that the expectations hypothesis holds in both BRICS and G7 country groups. In the long run, the short‑term interest rate is able to predict the long-term interest rate in both the BRICS and G7 countries. Interest rates in BRICS indicate rapid adjustment back to the long‑run equilibrium, while the adjustment is sluggish in the G7 block. Based on the findings of the study, the sluggish adjustment to the equilibrium in the G7 gives the impression that the financial crisis had an impact on the term structure of interest rates as the G7 countries were directly affected by the crisis.